2007
DOI: 10.1007/s00467-006-0380-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disturbances following the use of inadequate solutions for hemofiltration in acute renal failure

Abstract: Continuous renal replacement therapy (CRRT) has become an important supportive therapy for critically ill children with acute renal failure. In Turkey, commercially available diafiltration and replacement fluids cannot be found on the market. Instead, peritoneal dialysis fluids for dialysis and normal saline as replacement fluid are used. The first objective of this study was to examine metabolic complications due to CRRT treatments. The second objective was to determine demographic characteristics and outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The most commonly reported causes of ARF are congenital cardiac diseases, bone marrow transplantation, nephrotoxins, and sepsis. 17 In our study, 5.5% of the patient groups had primary renal impairment. Moreover, again in conformity with the literature, impairment depending on congenital cardiac disease was the most common one among the CRRT indications, and metabolic diseases were considered as a second indication.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The most commonly reported causes of ARF are congenital cardiac diseases, bone marrow transplantation, nephrotoxins, and sepsis. 17 In our study, 5.5% of the patient groups had primary renal impairment. Moreover, again in conformity with the literature, impairment depending on congenital cardiac disease was the most common one among the CRRT indications, and metabolic diseases were considered as a second indication.…”
Section: Discussionmentioning
confidence: 45%
“…Moreover, again in conformity with the literature, impairment depending on congenital cardiac disease was the most common one among the CRRT indications, and metabolic diseases were considered as a second indication. 17 Impairment being the most common cause depending on congenital cardiac disease was associated with renal ischemia developed after cardiogenic shock in the literature. 6 Outcome rate in the literature was reported as between 34 and 52% in patients receiving CRRT.…”
Section: Discussionmentioning
confidence: 99%
“…[4,19,20] while others suggested that correction of acidosis with lactatebuffered CVVHDF solutions. [4,11] Soysal et al [2] demonstrated that 1.36% PD solution induced metabolic acidosis when used as CVVHDF fluid. Our study confirms this previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if dextrose-containing PD solutions is used as dialysate in CRRT, roughly 45-60% of the dextrose is absorbed, and the high-glucose concentration in peritoneal dialysate may aggravate hyperglycemia. [12] Soysal et al [2] used PD solution as dialysate for CRRT in pediatric patients and demonstrated that hyperglycemia was the most common complication in these patients. Hyperglycemia increases mortality in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation